The 1st Aicif Asean International conference on Islamic finance "Islamic finance and its role in economic development and the creation of just and stable monetary system" - Islamic_Finance... (IIUM Institute of Islamic Banking & Finance {II/BF], 2013)
kh,2/ws.c.1-2